New climatic oscillations during MIS 11c in the record of the Skrzynka II site (Eastern Poland) based on palynological and isotope analysis. (20th September 2022) - Górecki, Artur; Żarski, Marcin; Drzewicki, Wojciech; Pleśniak, Łukasz; Zalewska-Gałosz, Joanna; Hrynowiecka, Anna
Abstract: Deposits of MIS 11c (Masovian Interglacial) are common in eastern Poland and therefore the area is considered as a Masovian palaeolakeland. In the Skrzynka II succession, MIS 11c lacustrine and MIS 10 lacustrine deposits of the early Liviecian Glaciation were found below beds representing the Weichselian Glaciation and the Holocene (1.35 m). The Mazovian Interglacial succession of the core as well as the base of the Liviecian Glaciation in depth interval 2.10–6.10 m were sampled for the purpose of palynological and isotope analyses. The main goal of the study was to determine a detailed record of climatic oscillations during MIS 11c. The palynological record of the Skrzynka II core contains nearly the entire MIS 11c succession, with an exception of the earliest protocratic stage. Both the previously described oscillation known from other European localities are present in the Skrzynka II record. Moreover, another major regressive oscillation, which was previously misinterpreted in two other Polish localities, was described in the late mesocratic phase. Yet another oscillation can be distinguished within the telocratic phase; it can be correlated with the 'birch oscillation' known so far only from Nowiny Żukowskie in Poland. Enhanced sampling resolution enabled also the description of several minor, local-scale climatic events or disturbances. Results of the isotope analysis correspond well with pollen data in the lower part of the succession, confirming a warming trend in the early interglacial and the cold character of the first regressive oscillation event. Since the second stage of the mesocratic phase, an unknown environmental disturbance occurred and δ 13 C(org) data are inconsistent with the pollen record until the end of the climatic optimum.